Controlled synthesis of polyethylenimine coated gold nanoparticles: Application in glutathione sensing and nucleotide delivery - Pandey P.C.; Pandey G.; Narayan R.J. (My University, 2025)
Synthesis of functional gold nanoparticles (AuNPs) justifying selectivity in biochemical interaction along with biocompatibility suited for in vivo biomedical applications has been a challenging issue. We report herein the role of polyethylenimine (PEI) in controlled synthesis of AuNPs under ambient conditions which has potentiality for sensing glutathione and selective interaction with DNA binding proteins facilitating endosomal escape for the nucleotide delivery. The choice of organic reducing agents like formaldehyde/acetaldehyde/acetyl acetone/tetrahydrofuran hydroperoxide and other similar compounds allow rapid conversion of PEI capped gold cations into AuNPs at room temperature thus controlling the functional ability of nanoparticles as a function of organic reducing agents. Both small and higher molecular weight PEI facilitates fast synthesis of AuNPs controlling cytotoxicity during in vivo biomedical applications. The AuNPs have been characterized by UV–Vis and transmission electron microscopy revealing excellent polycrystallinity and controlled nanogeometry. The cationic polymer coating enhances the electrocatalytic performances of nanoparticles. The typical biomedical application on glutathione (GSH) sensing based on peroxidase mimetic ability of as made AuNPs is studied. The as synthesized AuNPs are extreme salt and pH resistant and have potentiality for both homogeneous and heterogeneous biocatalysis. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1191–1199, 2017. © 2016 Wiley Periodicals, Inc.